(untitled) (Journal of Life and Earth Science, 2011)
Collembola are small soil dwelling apterygot (wingless) arthropod which are found all over the world and in a great variety of habitats, from seashore to the highest peaks of the mountains. There are over six thousands described collembolan species in about 500 genera worldwide. In this study 72 and 52 individuals belonging to the genera Rambutsinella and Entomobrya (Collembola: Entomobryidae), respectively were identified. Perhaps this constitutes the first report on collembolan in Bangladesh. Key words: Collembola; taxonomy; Entomobryidae; Rambutsinella; Entomobrya DOI: 10.3329/jles.v5i0.7347 J. Life Earth Sci., Vol. 5: 33-35, 2010